Legal Implementation of Domestic Violence: A Case Study of Military Justice and Social Issues in Ambon, Indonesia - Rahawarin, Fauzia; Jamaa, La; Kabalmay, Husin Anang; Lonthor, Ahmad (Journal of Ecohumanism, 2024)
Law enforcement of domestic violence (DV) cases involving members of the military in Indonesia presents unique and complex challenges, particularly as it involves the overlap between general criminal law and military criminal law. This study analyses the relevant legal foundations, namely the Military Criminal Code (KUHPM) and Law No. 23/2004 on the Elimination of Domestic Violence (PKDRT Law), in the context of handling domestic violence cases committed by members of the military. Using a case study method and interviews with victim-witnesses, this research reveals that the application of the law against domestic violence in the military often faces obstacles due to the military hierarchy and strict corps values. The research findings suggest the need for stronger integration between military and civilian legal frameworks, as well as policy reforms in the procedures for handling domestic violence cases in the military to ensure fairer and more transparent justice. In addition, the study also proposes the establishment of a special unit to handle domestic violence in the military, improved gender-sensitive training, and stricter implementation of a "Zero Tolerance" policy to prevent and effectively handle domestic violence cases. These reforms are expected to strengthen military integrity and discipline and protect the rights of victims of domestic violence in Indonesia.